Development of novel treatment strategies for inflammatory diseases- Similarities and divergence between glucocorticoids and GILZ - Qiang eCheng; Eric eMorand; Yuan Hang Yang (Frontiers Media S.A., 2014)
Glucocorticoids (GC) are the most commonly prescribed medications for patients with inflammatory diseases, despite their well-known adverse metabolic effects. Previously, it was understood that the anti-inflammatory effects of the GC/GC receptor (GR) complex were mediated via transrepression, whilst the adverse metabolic effects were mediated via transactivation. It has recently become clear that this 'divergent actions' paradigm of GC actions is likely insufficient. It has been reported that the GC/GR-mediated transactivation also contributes to the anti-inflammatory actions of GC, via up-regulation of key anti-inflammatory proteins. One of these is glucocorticoid-induced leucine zipper (GILZ), which inhibits inflammatory responses in a number of important immune cell lineages in vitro, as well as in animal models of inflammatory diseases in vivo. This review aims to compare the GILZ and GC effects on specific cell lineages and animal models of inflammatory diseases. The fact that the actions of GILZ permit a GILZ-based therapy to lack GC-like adverse effects presents the potential for development of new strategies to treat patients with inflammatory diseases.